2015
DOI: 10.1016/j.brs.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation Treatment in an Adolescent with Autism and Drug-Resistant Catatonia

Abstract: Catatonia is a syndrome characterized by alterations in motor, vocal and behavioral signs, generally occurring in the context of various medical and neuropsychiatric conditions [1]. Recent evidence suggests an increased recognition of catatonia as a comorbid syndrome of Autism Spectrum Disorder (ASD), with a prevalence ranging between 12% and 17% [2]. Although the nature of the association between these two conditions is still unclear, the cooccurrence of catatonic symptoms and ASD may be due to shared abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 9 publications
2
32
0
4
Order By: Relevance
“…The anode was placed over the left dorsolateral prefrontal cortex and the cathode over the right (1 mA for 20 min). This treatment protocol resulted in a 30% reduction of catatonic symptoms for 1 month after the end of treatment (Costanzo et al, 2015). Although further studies are needed, these findings point to the prefrontal cortex as a target for neuromodulation via tDCS, resulting in a noninvasive brain stimulation method with potential to modulate alterations in frontal lobe and its connectivity and, consequently, to reduce the frontal clinical manifestations of autism.…”
Section: Autismmentioning
confidence: 85%
See 1 more Smart Citation
“…The anode was placed over the left dorsolateral prefrontal cortex and the cathode over the right (1 mA for 20 min). This treatment protocol resulted in a 30% reduction of catatonic symptoms for 1 month after the end of treatment (Costanzo et al, 2015). Although further studies are needed, these findings point to the prefrontal cortex as a target for neuromodulation via tDCS, resulting in a noninvasive brain stimulation method with potential to modulate alterations in frontal lobe and its connectivity and, consequently, to reduce the frontal clinical manifestations of autism.…”
Section: Autismmentioning
confidence: 85%
“…With the same stimulation protocol, but applied in two single sessions of anodal tDCS separated by 1 week, improvements in the social scale and health and behavioral problems scale of the Autism Treatment Evaluation Checklist (but not in the language scale nor the sensory and cognitive awareness scale) and peak alpha EEG power have been described in children with the same age range ( Amatachaya et al, 2015). In a case study (Costanzo et al, 2015), an adolescent girl (14 years old) with autism and comorbid catatonia was treated by 28 daily tDCS sessions (each week from Monday to Friday), in association with the patient's usual medication (20 mg/day of promazine, 400 mg/day of quetiapine, and 600 mg/day of carbolithium). The anode was placed over the left dorsolateral prefrontal cortex and the cathode over the right (1 mA for 20 min).…”
Section: Autismmentioning
confidence: 98%
“…To date, only four studies (in addition to study by Gómez et al, 2017; see above) have applied tDCS in children or adolescent with ASD: 1 open-label, non-controlled study (Schneider and Hopp, 2011) addressing language impairments, two randomized sham-controlled studies by Amatachaya et al (2014, 2015) addressing ASD clinical symptoms and psychosocial functioning, and a case report (Costanzo et al, 2015) addressing drug-resistant catatonia in a patient with ASD.…”
Section: Methodsmentioning
confidence: 99%
“…In a case report, Costanzo et al (2015) described the effect of tDCS over the DLPFC in an adolescent girl (14 years old) with ASD and drug-resistant catatonia. Catatonia is a syndrome mainly featured by the presence of catalepsy, waxy flexibility, stupor, agitation, mutism, negativism, posturing, mannerism, stereotypies, grimacing, echolalia, echopraxia (American Psychiatric Association, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…In another crossover trial with 20 children showed significant improvements in both the Childhood Autism Rating Scale (CARS) and the ATEC with 20 minutes of left frontal 1 mA anodal tDCS [81]; 2 mA anodal stimulation for 30 minutes over the left DLPFC corresponded to improved syntax acquisition using the Bilingual Aphasia Test in 10 minimally verbal autistic children [82]. Moreover, 28 sessions of 1 mA tDCS for 20 minutes with the anode over F3 and cathode over F4 resulted in a month-long improvement in symptoms in a patient with ASD and drug-refractory catatonia [83]. …”
Section: Tdcs Therapeutic Potentialmentioning
confidence: 99%